A Recommended Guide to Students' Rights and Responsibilities in Michigan - Michigan State Dept. of Education, Lansing; Michigan State Dept. of Education, Lansing ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
These guidelines describe areas of concern as indicated by recent litigation, questions received from local school districts, and complaints received from parents and students. They also present, as a frame of reference, the status of current school law where and as it applies to the area of students' rights and responsibilities. The document is divided into five major sections: (1) background information and the purpose and need for such a document, (2) aspects of current law and practices relative to student behavior, (3) specific student behavior in terms of rights and responsibilities, (4) suspension of students along with guidelines for procedural due process, and (5) summary of the document with requests for continual review and reevaluation. (Author/MLF)
ERIC Note: Not available in hard copy due to marginal legibility of original document.
Educational level discussed: Elementary Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Corporal Punishment; Court Litigation; Dress Codes; Due Process; Elementary Secondary Education; Married Students; Police School Relationship; Pregnant Students; School Law; School Policy; Search and Seizure; Student Behavior; Student Publications; Student Records; Student Responsibility; Student Rights; Suspension; Michigan; Guides, General